CRISPR systems: what's new, where next?. (23rd December 2021) - Parkes, Ashley; Kemm, Fiona; He, Liu; Killelea, Tom
Abstract : The genetic signature of natural CRISPR-Cas systems were first noted in a 1989 publication and were characterized in detail from 2002 to 2007, culminating in the first report of a prokaryotic adaptive immune system. Since then, CRISPR-Cas enzymes have been adapted into molecular biology tools that have transformed genetic engineering across domains of life. In this feature article, we describe origins, uses and futures of CRISPR-Cas enzymes in genetic engineering: we highlight advances made in the past 10 years. Central to these advances is appreciation of interplay between CRISPR engineering and DNA repair. We highlight how this relationship has been manipulated to create further advances in the development of gene editing.